Extended-spectrum β-lactamase Enterobacteriaceae (ESBLE) in intensive care units: strong correlation with the ESBLE colonization pressure in patients but not same species. Issue 1 (January 2020) - Lemarié, C.; Legeay, C.; Lasocki, S.; Mahieu, R.; Kouatchet, A.; Bahier, L.; Onillon, L.; Corre, M.; Kempf, M.; Eveillard, M.
Summary: Sink drains of six intensive care units (ICUs) were sampled for screening contamination with extended-spectrum β-lactamase-producing Enterobacteriaceae (ESBLE). A high prevalence (59.4%) of sink drain contamination was observed. Analysing the data by ICU, the ratio 'number of ESBLE species isolated in sink drains/total number of sink drains sampled' was highly correlated (Spearman coefficient: 0.87; P = 0.02) with the ratio 'number of hospitalization days for patients with ESBLE carriage identified within the preceding year/total number of hospitalization days within the preceding year'. Concurrently, the distribution of ESBLE species differed significantly between patients and sink drains.